2011
DOI: 10.1123/jsep.33.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Athlete Narcissism in Moderating the Relationship Between Coaches’ Transformational Leader Behaviors and Athlete Motivation

Abstract: Leadership research that examines follower characteristics as a potential moderator of leadership effectiveness is lacking. Within Bass’s (1985) transformational leadership framework, we examined follower narcissism as a moderator of the coach behavior–coach effectiveness relationship. Youth athletes (male = 103, female = 106) from the Singapore Sports Academy (mean age = 14.28, SD = 1.40 years) completed the Differentiated Transformational Leadership Inventory (Callow, Smith, Hardy, Arthur, & Hardy, 2009)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 57 publications
3
88
0
2
Order By: Relevance
“…Evidence exists to suggest that coaches' use of TFL behaviours is linked with positive psychosocial outcomes, including athlete satisfaction, effort, motivation, and group cohesion (Arthur, Woodman, Ong, Hardy, & Ntoumanis, 2011;Callow, Smith, Hardy, Arthur, & Hardy, 2009;Charbonneau, Barling, & Kelloway, 2001;Rowold, 2006). Of particular relevance to PYD research, Vella et al (2013) demonstrated that TFL may foster youth's personal development as higher ratings of coach TFL behaviours were associated with the development of personal and social skills, cognitive skills, goal setting skills, and initiative.…”
mentioning
confidence: 92%
“…Evidence exists to suggest that coaches' use of TFL behaviours is linked with positive psychosocial outcomes, including athlete satisfaction, effort, motivation, and group cohesion (Arthur, Woodman, Ong, Hardy, & Ntoumanis, 2011;Callow, Smith, Hardy, Arthur, & Hardy, 2009;Charbonneau, Barling, & Kelloway, 2001;Rowold, 2006). Of particular relevance to PYD research, Vella et al (2013) demonstrated that TFL may foster youth's personal development as higher ratings of coach TFL behaviours were associated with the development of personal and social skills, cognitive skills, goal setting skills, and initiative.…”
mentioning
confidence: 92%
“…Research attention has supported the predictive qualities of transformational leadership in sport (e.g., Arthur, Woodman, Ong, Hardy, & Ntoumanis, 2011;Rowold, 2006). For instance, Rowold demonstrated that transformational behaviours of martial arts coaches led to elevated perceptions of coach effectiveness in comparison to transactional behaviours.…”
Section: A Social Identity Approach To Leadership In Sport 15mentioning
confidence: 99%
“…Although a range of sport-specific models of leadership have been proposed-in particular, the Multidimensional Model of Leadership [136] and the Mediational Model of Leadership Behavior [137]-more recent work has focused on the importance of transformational leadership [138][139][140][141][142][143], with its distinct emphasis on the leader-follower relationship. Yet despite the promise that transformational leadership might hold for sport-e.g., in advancing beyond simple transactional or exchange theories of leadership-critics have questioned both its focus on charismatic leadership [144] and its rather vague theoretical underpinnings [145].…”
Section: Social Identity Is the Basis For Sports Group Leadershipmentioning
confidence: 99%